Status epilepticus results in persistent overproduction of reactive oxygen species, inhibition of which is neuroprotective. (10th September 2015) - Williams, S.; Hamil, N.; Abramov, A.Y.; Walker, M.C.; Kovac, S.
Highlights: Reactive oxygen species (ROS) are elevated after status epilepticus and in epilepsy. ROS contribute to cell seizure-induced cell death. NADPH oxidase produces ROS during seizure activity. NADPH oxidase inhibition with AEBSF, reduces cell death in an in vivo epilepsy model. Abstract: Epilepsy and seizure activity result in the generation of reactive oxygen species (ROS), which contribute to seizure-induced neuronal damage. Recent in vitro evidence indicates that NADPH oxidase contributes significantly to seizure-induced ROS. We further tested this in rat glio-neuronal cultures and in ex vivo chronic epileptic rat brain tissue using live cell-imaging techniques. Here, we show that ROS are upregulated in chronic epilepsy and that ROS production contributes to cell death, which is seen after status epilepticus (SE) and chronic seizures. Inhibition of ROS production by AEBSF, a NADPH oxidase inhibitor, markedly reduced seizure-induced cell death in the perforant path model of epilepsy. These findings demonstrate a critical role for ROS, generated by NADPH oxidase, contributing to seizure-induced cell death. These findings point to NADPH oxidase inhibition as a novel treatment strategy to prevent brain injury in SE and chronic epilepsy.